The Representation of Patriarchy in the Movie Enola Holmes 1: A Feminist Literary Criticism - Thalia Ayu Wardani, Dea; Gusthini, Misyi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
Patriarchy is a form of cultural domination that generates gender inequality within society. In this culture, patriarchy is understood as a social system that places men in dominant positions, thereby producing gender disparities. As a result, women experience inequality in various aspects of life. In response to this condition, the feminist movement emerged as a form of resistance against such disparities, aiming to advocate for and strengthen women's rights. This study seeks to examine the representation of patriarchy in the film Enola Holmes 1 using Sylvia Walby's theory of the six structures of patriarchy (1990). A qualitative descriptive method was employed, with data collected through observation of dialogues using a feminist literary criticism approach, particularly focusing on the concept of radical feminism. The findings reveal eight pieces of evidence that represent three main categories of radical feminism: (1) resistance against patriarchy, demonstrated through the rejection by female characters of male control and restrictive social structures; (2) rejection of traditional gender roles, reflected in Enola's refusal to conform to the idealized image of Victorian women; and (3) self-empowerment and personal autonomy, visible through Enola’s awareness and actions in determining her own future without submitting to patriarchal norms. These findings affirm that Enola Holmes 1 not only presents feminist issues but also illustrates the struggle for women's liberation from patriarchal structures embedded within familial, cultural, and political domains.